Trendsetter Komunikasi di Era Digital: Tantangan dan Peluang Pendidikan Komunikasi dan Penyiaran Islam - Venny Eka Meidasari, Andi Faisal Bakti dan (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
The increasing penetration of so-called new media has undermined the global boundary, giving rise to the liberalization of information. This reality results in the rise of the era of the information society, and has led people across the world, including Muslims in Indonesia, to deal with the demands of the era. Therefore, attempts to create strategies to take benefits from those new media and to reduce their negative impacts are important. This paper discusses the challenges and opportunities of Islamic communication in the midst of today's digital era. Central to this analysis are kinds of communication trendsetter among Muslims in this country.Keywords: Communication trendsetter, digital era, Islamic communication and broadcast———————————————————————-Penetrasi new media (media baru) yang mengglobal seakan meruntuhkan dinding-dinding pembatas dan menjadikannya sebagai sekat liberalisasi informasi. Realitas ini telah membawa masyarakat, termasuk masyarakat Mus-lim di Indonesia masuk ke dalam era masyarakat informasi, sehingga pengendalian yang tepat untuk memanfaatkan new media dan mengeliminir dampaknya menjadi penting. Tulisan ini mendiskusikan tantangan dan peluang komuni-kasi dan peyiaran Islam di tengah-tengah era digital saat ini.Kata Kunci: trendsetter komunikasi, era digital, komunikasi dan penyiaran Islam